Influence of Different Excavation Sequence of Double-Side Heading Method on Supporting Structure - Chengkun Ling; Yanmei Ruan; Pengbo Wu; Jin Li; Jin Zhao; Bingxiang Yuan (Advances in Civil Engineering)
The double-side heading method is often used in the construction of large-span and large-section tunnels. The excavation of the pilot tunnel is complex, so the construction efficiency is low. Based on the underground excavation tunnel project of a subway in Guangzhou, the section excavation sequence of the traditional double-side heading method is optimized according to the actual situation. Midas/GTS software is used for finite element analysis, the displacement and internal force of ground settlement and support structure under two different section excavation sequences are calculated, and the calculation results are compared with the field monitoring data. The calculation results show that the influence of the two excavation sequences on the displacement of the supporting structure is not much different, but the influence on the internal force of the supporting structure is obviously different. The stress value of the supporting structure caused by the optimized excavation sequence is larger, especially the temporary inverted arch, but it is within the controllable range. The optimized excavation sequence increases the construction work surface, greatly improves the construction efficiency, and reduces the project cost, which can provide a reference for the construction of urban subway tunnels under similar engineering conditions in the future.